2020
DOI: 10.21037/gs-20-530
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of multiparametric ultrasound in parotid gland evaluation

Abstract: Disorders affecting parotid gland represent a heterogeneous group comprising congenital, inflammatory and neoplastic diseases which show a focal or diffuse pattern of appearance. The differentiation of neoplastic from non-neoplastic conditions of parotid glands is pivotal for the diagnostic imaging. Frequently there is evidence of overlapping between the clinical and the imaging appearance of the various pathologies. The parotid gland is also often object of study with the combination of different techniques [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 128 publications
0
9
0
2
Order By: Relevance
“…On Doppler US, malignant tumors and Warthin tumors have rich vascularization, whereas pleomorphic adenoma appears reduced vascularization. One study reported that there was appreciable overlap between the US features of benign tumors and that of malignant tumors within the histological heterogeneous [ 19 ]. Therefore, it is difficult to differentiate malignant and benign lesions based on B-mode and Doppler US.…”
Section: Discussionmentioning
confidence: 99%
“…On Doppler US, malignant tumors and Warthin tumors have rich vascularization, whereas pleomorphic adenoma appears reduced vascularization. One study reported that there was appreciable overlap between the US features of benign tumors and that of malignant tumors within the histological heterogeneous [ 19 ]. Therefore, it is difficult to differentiate malignant and benign lesions based on B-mode and Doppler US.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was a correlation between the micro-and the macro-vascularization of the lesions respectively evaluated with CEUS and Color-Doppler US, but the predictive value of each single technique was not so effective and a multiparametric assessment was required to increase the specificity and PPV in the diagnosis of malignant parotid lesions and the sensitivity in the differential diagnosis between pleomorphic adenomas and Warthin's tumors [37]. Another recent review confirmed that MPUS, specially if includes CEUS, enables the differential diagnosis of parotid tumors [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…We also tried to identify a specific pattern of vascularization in order to distinguish between benign lesions as follows: marked and homogeneous vascularization for Warthin's tumor while mild and peripheral flow for pleomorphic adenoma [19][20][21]. USE USE was performed using a semi-quantitative quasistatic technique by the same experienced radiologist.…”
Section: B-mode Us and Color-doppler Usmentioning
confidence: 99%
“…Dies zeigt die Herausforderung in der sonografischen Differenzialdiagnostik einer neu aufgetretenen Läsion. der Regel aber gut möglich [36,37]. Auch die Unterscheidung der Lage einer Läsion (intra-versus extraglandulär, superfiziell versus tief) gelingt problemlos unter Beachtung wichtiger Landmarken (z.…”
Section: Solide Tumoren Der Speicheldrüsenunclassified
“…▶ Tab. 3 Sonografische Charakteristiken der häufigsten Tumorentitäten der Speicheldrüsen [22,36,41,42,43]. Zur besseren Übersichtlichkeit werden entzündliche (akute Lymphadenitis, seltene Infektionserkrankungen, Abszesse) von malignen Lymphknotenerkrankungen (Lymphome und Metastasen) unterschieden.…”
Section: Lernzielunclassified